Ligne, sensation et métaphore dans la peinture persane du XVe siècle - Balafrej, Lamia (RACAR : Revue d'art canadienne / Canadian Art Review, 2020)
This article explores the tension between sensation and representation in Persian painting, and the role of the line in expressing and embodying the metaphorical possibilities of the medium. Persian painting from the fifteenth century has most often been approached as illustrative, a grid of figures and motifs representing fixed meanings. This paper argues that Persian painting’s system of representation, although seemingly articulated into differentiated signs, cannot be reduced to a pre-given text. Using primary sources that illuminate the terms in which Persian painting and drawing could be described by their historical audiences, I reveal that contemporary viewers were also attentive to the sensory work of the artist, especially visible in the line’s materiality. Examining the lyrical verve of each motif’s contour, the period eye uncovered the artists’ sensation, as well as a series of images linking the line to the artist’s bodily movements, the face of the beloved, and the pursuit of mystical desire.